Needs Analysis for the Development of E-Modules Argument Driven Inquiry Contextualized Socio Scientific Issues to Empower Students' Scientific Argumentation Skills - Resi, Damasus Nosi; Sutarno; Indrowati, Meti (Journal of Educational Sciences, 2025)
This study aims to analyze the need for developing E-modules Argument Driven Inquiry (ADI) with Socio Scientific Issues (SSI) context on environmental change material to empower students' scientific argumentation skills. The research method used is descriptive qualitative method with data collection techniques through interviews and questionnaires. The subjects of this study were biology teachers and 60 students of SMA Negeri 4 Surakarta. The results of the needs analysis showed that teachers and students need technology-integrated teaching materials in the form of ADI E-modules with SSI context on environmental change material. The development of ADI E-modules with SSI context is expected to be an alternative learning solution that is innovative and effective in improving the quality of biology learning which has implications for empowering students' scientific argumentation skills.